Electroadsorption of Arsenic from Natural Water in Granular Activated Carbon - Beralus, Jean-Mackson; Ruiz-Rosas, Ramiro; Cazorla-Amorós, Diego; Morallón, Emilia (Frontiers in Materials, 2014)
The adsorption and electroadsorption of arsenic from a natural water has been studied in a filter-press electrochemical cell using a commercial granular activated carbon as adsorbent and Pt/Ti and graphite as electrodes. A significant reduction of the arsenic concentration is achieved when current is imposed between the electrodes, especially when the activated carbon was located in the vicinity of the anode. This enhancement can be explained in terms of the presence of electrostatic interactions between the polarized carbon surface and the arsenic ions, and changes in the distribution of most stable species of arsenic in solution due to As(III) to As(V) oxidation. In summary, electrochemical adsorption on a filter-press cell can be used for enhancement the arsenic remediation with activated carbon in the treatment of a real groundwater.